2018
DOI: 10.18187/pjsor.v14i2.1929
|View full text |Cite
|
Sign up to set email alerts
|

Regression Modeling of Competing Risks Survival Data in the Presence of Covariates Based on a Generalized Weibull Distribution: A Simulation Study

Abstract: In survival analysis or medical studies each person can be exposed to more than one type of outcomes which occurrence of one of them prevents the other outcomes' occurrence; this situation is called the competing risks. Assessing the effect of covariates on the survival time (or failure time) is one of the purposes in competing risks analysis. In this paper, we study a competing risks model in the presence of covariates when the causes of failures follow generalized Weibull distributions. Covariates are entere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…However, postdiagnosis BMI was not associated with CRC mortality [29]. In a retrospective study in Iran, the results indicated that the BMI had a statistically significant GMJ.2019;8:e1413 www.gmj.ir effect on survival time, and decreasing BMI would increase the risk of patient's death from CRC [30]. In this study, the BMI has a meager significant impact on cure rate of patients with CRC; thus, an increase in BMI leads to a slight increase in cure probability of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, postdiagnosis BMI was not associated with CRC mortality [29]. In a retrospective study in Iran, the results indicated that the BMI had a statistically significant GMJ.2019;8:e1413 www.gmj.ir effect on survival time, and decreasing BMI would increase the risk of patient's death from CRC [30]. In this study, the BMI has a meager significant impact on cure rate of patients with CRC; thus, an increase in BMI leads to a slight increase in cure probability of patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies revealed that the risk of death is undistinguishable for men and women as well [18][19][20][21]…”
Section: Based On An Examination Of Numerous Factorsmentioning
confidence: 99%